2018
DOI: 10.1093/molbev/msy043
|View full text |Cite
|
Sign up to set email alerts
|

The Amount of Nitrogen Used for Photosynthesis Modulates Molecular Evolution in Plants

Abstract: Genome and transcript sequences are composed of long strings of nucleotide monomers (A, C, G, and T/U) that require different quantities of nitrogen atoms for biosynthesis. Here, it is shown that the strength of selection acting on transcript nitrogen content is influenced by the amount of nitrogen plants require to conduct photosynthesis. Specifically, plants that require more nitrogen to conduct photosynthesis experience stronger selection on transcript sequences to use synonymous codons that cost less nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 80 publications
1
39
0
1
Order By: Relevance
“…Accordingly, plant genomes and proteomes are AT-rich and contain amino acids that require fewer nitrogen atoms as compared with animal genomes and proteomes. This fits well with the fact that nitrogen sources are limited for plants, while animals can access organic sources of nitrogen [23,36,37]. Of note, in eukaryotic genes containing introns, exons and introns have the same composition bias [79].…”
Section: Evolution Of the Genetic Code: Co-adaptation Of Nucleic Acidsupporting
confidence: 80%
See 2 more Smart Citations
“…Accordingly, plant genomes and proteomes are AT-rich and contain amino acids that require fewer nitrogen atoms as compared with animal genomes and proteomes. This fits well with the fact that nitrogen sources are limited for plants, while animals can access organic sources of nitrogen [23,36,37]. Of note, in eukaryotic genes containing introns, exons and introns have the same composition bias [79].…”
Section: Evolution Of the Genetic Code: Co-adaptation Of Nucleic Acidsupporting
confidence: 80%
“…As for proteins, environmental physicochemical parameters (temperature and chemical composition) constrain the nucleotide composition of genomes and this can be observed in thermophilic, halophilic, acidophilic, aerobic, and radiation-exposed organisms [28,35]. Finally, the amount of DNA per cell (genome size and ploidy) is constrained by the environmental availability of phosphorus, and the genomes of organisms growing in a nitrogen-poor environment are enriched in A:T pairs, which require seven nitrogens instead of the eight used in G:C pairs [36][37][38].…”
Section: Physicochemical Constraints On Nucleic Acid Polymer Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the ecophysiological significance of angiosperms' higher PNUE (Lusk et al, 2003), recent evidence has also suggested a strong link between PNUE and the rate of molecular evolution. Kelly (2018) showed that species that overinvest in N for their photosynthetic enzymes (i.e. gymnosperms in our study with high V Cmax, 20°C values; Supplemental Table S2) evolve slowly, while species that reduced N investment (i.e.…”
Section: Discussionmentioning
confidence: 72%
“…To biosynthesize the precursors of these biomacromolecules, plants must integrate inorganic carbon (CO 2 ) and nitrogen (NO 3 − /NH 4 + ); however, compared to CO 2 , NO 3 − /NH 4 + is more difficult to obtain from the environment. Therefore, plant growth is generally nitrogen limited in both natural and agricultural environments [46]. The extensive use of synthetic fertilizers in developed countries is expensive and environmentally damaging.…”
Section: Discussionmentioning
confidence: 99%